2012
DOI: 10.1007/s00432-012-1331-y
|View full text |Cite
|
Sign up to set email alerts
|

New indication for therapeutic potential of an old well-known drug (propranolol) for multiple myeloma

Abstract: Purpose Propranolol, a non-selective b-adrenergic receptor blocker, has been used for the treatment of the patients with hypertension for more than 50 years. There are several in vitro and in vivo evidences that b-adrenergic receptor antagonists inhibit proliferation and angiogenesis and also increase apoptosis in breast, skin, and colon cancers. The aim of this study was to investigate the cytotoxic and apoptotic effects of propranolol and the genes involved in propranololinduced apoptosis in multiple myeloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
(61 reference statements)
3
17
0
1
Order By: Relevance
“…The adverse effects of propranolol are mild and manageable with long-term use [14]. Although an antimyeloma effect was first reported last year [11], the antitumor effect is consistent with results obtained with other solid-tumor models including breast cancer, acute leukemia, neuroblastoma, etc. [4,10,15,16].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The adverse effects of propranolol are mild and manageable with long-term use [14]. Although an antimyeloma effect was first reported last year [11], the antitumor effect is consistent with results obtained with other solid-tumor models including breast cancer, acute leukemia, neuroblastoma, etc. [4,10,15,16].…”
Section: Discussionsupporting
confidence: 74%
“…Until now, there are only a few reports on the effect of catecholamine and the β-receptor on MM cells. Only one research group found that propranolol, a nonspecific β-receptor antagonist, inhibits myeloma cell proliferation and induces cell apoptosis in vitro [11]. …”
Section: Introductionmentioning
confidence: 99%
“…We contributed to highlight the drug deleterious effects on mitochondrial network functions and dynamics in various cancer cells [44, 45], but Prop mechanism of action remained non-elucidated in breast cancer cells. Here, we showed that Prop induces apoptosis in various breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Kozanoglu et al investigated the in vitro effect of PRO on the U266 human multiple myeloma cell line [70]. They showed a dose and time dependent effect on cell proliferation and apoptosis, with IC50 values of 141, 100, and 75 μM after 24-, 48-, and 72-h PRO exposure, respectively.…”
Section: Pre-clinical Evidence In Cancer - In Vitro and In Vivomentioning
confidence: 99%